Fairness consideration of bandwidth scheduling for real-time services in IEEE 802.16m wireless networks - Jenhui Chen; Woei-Hwa Tarn; Jiann-Der Lee (2013 International Conference on Computational Problem-Solving (ICCP), 2013)
Although the scheduling problem of the uplink transmission in the IEEE 802.16 broadband wireless access standard has been extensively discussed, most of the results focus on the quality of service (QoS) issues, e.g. throughput and delay requirement. In real-time services, violent variance of bandwidth request usually triggers some problems of resource allocation, especially when the system bandwidth is saturated. In this paper, we introduce a fair scheduling algorithm named contribution-based scheduling algorithm (CSA) for uplink realtime polling service (rtPS). In this algorithm, a mobile subscriber (MS) is endowed with a contribution credit value at the end of each frame, which is based on the MS's contribution to the system resource utilization. The base station (BS) will allocate system resource according to the credit value. With the proposed fair scheduling algorithm, we guarantee the fairness, delay requirement and bandwidth utilization at the same time which cannot be fully achieved in existing studies.